2013
DOI: 10.1097/ico.0b013e31829e1e8c
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Epithelial Closure After PRK Associated With Topical Besifloxacin Use

Abstract: All the patients treated with besifloxacin 0.6% on the stromal bed exhibited significant problems with corneal epithelial healing and delayed visual recovery. We caution the use of besifloxacin 0.6% underneath a BCL during a PRK or other ocular surface surgeries requiring corneal epithelial debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This maintains the concentrated BAK in contact with the corneal surface for a prolonged period, which may result in increased toxicity. 35–37 The use of ketotifen and besifloxacin also coincides with our patient’s worst symptoms.…”
Section: Discussionsupporting
confidence: 66%
“…This maintains the concentrated BAK in contact with the corneal surface for a prolonged period, which may result in increased toxicity. 35–37 The use of ketotifen and besifloxacin also coincides with our patient’s worst symptoms.…”
Section: Discussionsupporting
confidence: 66%
“…However, problems with the prophylactic use of besifloxacin in the surgical setting have been reported under particular circumstances. Talamo et al [ 91 ] reported delayed epithelial closure (5 to 13 days, with an average of 8.8 days) and delayed visual recovery in a case series of 4 patients (7 eyes) treated with besifloxacin 0.6% instilled underneath a bandage contact lens (BCL) placed at the conclusion of photorefractive keratectomy (PRK) [ 91 ]. These adverse reactions were attributed by the authors to potential toxic effects of DuraSite or the preservative benzalkonium chloride 0.01% on exposed corneal stroma, especially when drug contact time is prolonged.…”
Section: Resultsmentioning
confidence: 99%
“…Delay in postoperative re-epithelialization has been shown to increase the risk of infection and haze after PRK. 19 One eye in the Tars_DCL 4wk group and one of the contralateral eyes (that had PRK and no other intervention) had an epithelial defect at postoperative week 1 both of which re-epithelialized the following week. By contrast, 3 eyes of 6 eyes in the Tars group (n = 6) had epithelial defects at postoperative week 1.…”
Section: Safetymentioning
confidence: 96%